Brazil : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper and Statistical Appendix on Brazil looks at price developments following the floating of the Real in mid-January 1999. The paper highlights that the experiences in East Asia-Indonesia, Korea, Malaysia, Philippines, and Thailand-all show that the pass-through from devaluation to inflation has been lower than expected, with the exception of Indonesia. The paper analyzes the competitiveness and export performance of Brazil. Effects of high interest rates and currency depreciation on Brazilian enterprises are also analyzed.